Transformation of Mortgage Rights Registration by Electronic System - Sumanto, Listyowati; Eka Sihombing, Irene; Pandamdari, Endang; Mariane, Irene; Kartikasari, Elsi (KnE Social Sciences, 2024)
On entering the digital era, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency introduced electronic land services, including electronic mortgage rights. To facilitate investment needs by applying for bank loans and to improve mortgage rights services in meeting the principles of transparency, timeliness, speed, convenience, effectiveness, and efficiency. This research aims to describe and analyze the arrangement of electronic mortgage rights system services, and the advantages and disadvantages faced by the organizers and users of the electronic mortgage rights system services. The type of research used is descriptive normative legal research. Secondary data were analyzed qualitatively. For the conclusion deductive logic was used. The research results showed that the types of services in the electronic mortgage rights system include registration of mortgage rights, transfer of mortgage rights, change of creditor name, and cancellation of liability electronically integrated mortgage rights service mechanisms. The land deed officials, creditors, and the land office experienced problems while registering mortgage rights in the electronic system. There are advantages and disadvantages to an electronic mortgage rights system. There are unclear settings. It is proposed that the rules regarding electronic mortgage rights must be revised regarding the improvement period for electronic mortgage rights applications. The provisions of Article 10 paragraph (3) of the Mortgage Rights Law cannot be implemented because the Electronic Mortgage Rights are based on land data that has been legalized and registered with the local land office. The provisions of Article 10 paragraph (3) of the Mortgage Rights Law must accommodate. Keywords: mortgage rights, registration, electronic system, advantages, disadvantages